Role Overload and Work Performance: The Role of Psychological Strain and Leader–Member Exchange - Tang, Wei-Gang; Vandenberghe, Christian (Frontiers in Psychology, 2021)
The relation between role overload and work performance remains insufficiently understood. Drawing upon conservation of resources theory, we expected role overload to negatively relate to performance through psychological strain and this relation to be buffered by leader-member exchange (LMX). Study 1 (N = 212) examined depression as a severe type of strain that mediates between role overload and in-role performance, job dedication, and voice behavior. Study 2 (N = 191) used generic, perceived strain as a mediator between role overload and in-role performance and reward recommendations. Both studies tested LMX’s buffering effect, controlling for role ambiguity and conflict. A supplementary panel study (N = 99) assessed the temporal relationship between role overload and strain. Role overload triggered psychological strain, which undermined performance, and LMX acted as a buffer on role overload, but not on role ambiguity or role conflict. We discuss the implications of these findings for theory and practice.